Experiments in keypad-aided spelling recognition - Parthasarathy, Sarangarajan (Acoustics, Speech, and Signal Processing, 2004. Proceedings.(ICASSP'04). IEEE International Conference on, 2004)
Accurate recognition of spellings is necessary in many call-center applications. Recognition of spellings over the telephone is inherently a difficult task and achieving very low error rates, using automatic speech recognition, is difficult. Augmenting speech input with input from the telephone keypad can reduce the error rate significantly. A variety of schemes for combining the keypad and speech input are presented. Experiments on a name entry task show that spellings can be recognized nearly perfectly using combined keypad and speech input, especially when a directory lookup is possible.